Psychological and social evaluation in cases of deliberate self-poisoning seen in an accident department. Issue 6314 (13th February 1982) - Gardner, R; Hanka, R; Roberts, S J; Allon-Smith, J M; Kings, A A; Nicholson, R
Abstract : The outcome in 115 consecutive patients with mild self-poisoning seen by junior medical staff and discharged from the accident department was compared with that of 98 similar patients admitted to the medical wards. Psychiatrists saw only four patients in the accident department and 25 admissions. In making their assessments the junior medical staff considered psychosocial factors as well as the patients' physical condition. Most patients recommended for further care, and discharged from the accident department, subsequently received it. Repetition rates were similar in the two groups and there had been no suicides when patients were followed up at one year. It is feasible for junior staff in an accident department to decide whether patients with self-poisoning need admission or may be discharged with or without subsequent referral for psychiatric or social work help.